2022
DOI: 10.3390/app12189306
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Thermo-Structural Analysis of Lightweight Concrete and Steel Decking Composite Slabs under Fire Conditions: Numerical and Experimental Comparison

Abstract: Composite slabs with steel decking profiles are widely used in building construction. However, the literature on the fire resistance of lightweight concrete (LWC) composite slabs with steel decking is limited. In this work, the thermo-structural performance of LWC composite slabs with trapezoidal steel decking was studied under fire conditions. A total of 12 experimental fire tests were carried out using specimens of 160 mm thickness, 1120 mm width and 2030 mm length, in which nine composite slabs were made of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…In addition, the development of foamed concrete with high-strength characteristics as performed by Namsone et al [1], Khan et al [2], Wei et al [3] and Xian et al [4] indicate promising results. Previous investigations by Liu & Tian [5], Abbas et al [6] and Martinez-Martinez [7] pointed out that the performance of lightweight composite slabs is closely in line with and comparable to that of other types of floor systems.…”
mentioning
confidence: 58%
“…In addition, the development of foamed concrete with high-strength characteristics as performed by Namsone et al [1], Khan et al [2], Wei et al [3] and Xian et al [4] indicate promising results. Previous investigations by Liu & Tian [5], Abbas et al [6] and Martinez-Martinez [7] pointed out that the performance of lightweight composite slabs is closely in line with and comparable to that of other types of floor systems.…”
mentioning
confidence: 58%
“…In terms of bond strength, there is an insignificant difference between lightweight composite slabs and conventional composite slabs. A nonlinear thermos-structural analysis by Martinez-Martinez [4] showed that lightweight composite slabs do not meet the minimum bearing capacity of 30 minutes required by BS EN 1994-1-2 [29]. The lightweight concrete was produced from siliceous aggregates and expanded clay, and achieves a compressive strength of around 25 MPa to 30 MPa.…”
Section: Lightweight Composite Slabsmentioning
confidence: 99%
“…Since this experimental study focuses on the structural behaviour, the three-point bending test has proven to be appropriate. Previous researcher such as Martinez-Martinez [4], Holy et al [47] and Kita et al [48] also used the three-point bending test to measure the bending stresses and maximum deflection of slab specimens. The three-point bending test, as shown in Fig.…”
Section: Experimental Testsmentioning
confidence: 99%
“…When regarding to the fire performance, however, such slabs behave similarly to plain concrete slabs in fire condition [1] and fail to meet the fire resistance requirements specified in Eurocode 4 [2] without using any reinforcement or fire proof coatings. Furthermore, extensive research has been conducted to explore the incorporation of various materials into composite slabs, including lightweight concrete [3][4] and recycled concrete [5]. These studies have demonstrated that the shielding effect of the profiled steel sheeting significantly influences the fire resistance of composite slabs.…”
Section: Introductionmentioning
confidence: 99%